The Application of Higher Order Thinking Skills in Teaching Reading at SMAN 7 Kediri - Cynthia Untsa Libasa; Khoiriyah Khoiriyah; Mahendra Puji Permana Aji (UM Purwokerto Press, 2023)
The teacher must refresh his understanding of incorporating HOTS into their teaching reading methods. When teaching reading in the classroom, the teacher always has challenges with the teaching process to students. The teacher has been working under very difficult situations with the student, limited teaching materials, and unanticipated student attendance. The purpose of this research are to describe the application of HOTS, identify the challenges faced by the teacher, and how does the teacher solve the challenges in the application of HOTS in teaching reading at SMAN 7 Kediri. In this research, the writer used the qualitative research design to collect data. The research was done in a day using observation by taking video and interview. The findings of this research are as follows: (1) the application of HOTS in teaching reading by starting from involvement of students in thinking or questioning with the teacher after the reading process. Then talk and share ideas with friends in a group discussion before writing. (2) the challenges faced by the teacher are limited vocabulary, time, materials, and lack of motivation by the student (3) the teacher should explore various resources such as textbooks, online platforms, or libraries. The writer suggests that the teacher should study about different method and other ways that can solve the problem in teaching reading. For that reason, it can be useful for every teacher after reading explanations about the application of HOTS and ways to solve the problem while teaching reading in the class.